ANALISIS KEPUASAN KONSUMEN DAN BAURAN PEMASARAN PADA AGROINDUSTRI KOPI BUBUK CAP JEMPOL DI KOTA BANDAR LAMPUNG - Putri, Vita Dwi; Affandi, Muhammad Irfan; Nikmatullah, Dewangga (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
This study aims to analyze the level of consumer satisfaction of coffee powder and the marketing mix of coffee powder agroindustry in Bandar Lampung City. The research method used was a case study. Research location was determined purposively. The number of interviewed samples was 60 respondents chosen using snowball sampling method. Respondents of this study consisted of consumers of coffee powder, owners, industry and trade in Bandar Lampung City, and experts of University Lampung chosen using snowball sampling. The study was conducted in February-April 2018. The data analysis methods used are the analysis of the Customer Satisfaction Index (CSI) and descriptive analysis. The results showed that: consumers of Jempol brand coffee powder in Bandar Lampung City were in satisfied criteria. The marketing mix for agroindustry has implemented marketing strategy (marketing mix). Key words: agroindustry, consumer satisfaction, coffee powder, marketing mix